Flow and heat transfer of supercritical RP-3 kerosene in an inclined rectangular channel heated on one side. (April 2022) - Yu, Jia-Jia; Jiang, Lie-Bin; Yu, Jin; Yu, Bin-Bin; Li, You-Rong
Abstract: The flow and heat transfer of the supercritical RP-3 kerosene in inclined rectangular channel was investigated by a series of the three-dimensional numerical simulations. The inclined rectangular channel is only heated on the one side by the heat flux ranging from 500 kW/m 2 to 640 kW/m 2 . The inclination angle of the rectangular channel varies from −90° to 90°. The results show that the evolution of the secondary flow along the main flow direction strongly depends on the inclination angle. In addition, the evolution of the secondary flow in vertical channels is much more complex than that in the inclined and horizontal ones. The average velocity of the secondary flow near the inlet of the heating section decreases with the increase of the inclination angle, while it increases firstly and then decreases after the inlet of the heating section with the increase of inclination angle. The secondary flow is enhanced by the increase of the heat flux. The severe thermal stratification always appears in the rectangular channels at all inclination angles. The minimum local heat transfer coefficient always appears near the walls at x  = ±1 mm slightly after the inlet of the heating section, while the maximum one locates at x  = 0 mm of the inlet of the heating section. The average heat transfer coefficient decreases first and then increases with the increase of heat flux and decrease of the inclination angle.